The Monitor Model Revisited: Evidence from Process Research - Tirkkonen-Condit, Sonja (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractResearch on human translation processes to date reveals that there are many routes to successful performance and that consciousness raising helps to identify undesirable tendencies and routines. Research on translation processes also shows that expertise calls for monitoring skills and self-awareness. This paper focuses on the monitor model of translation and reports on empirical evidence that supports the model. It shows that tendencies towards literal translation emerge in the products and processes of novices and experts alike. It also argues for further research into the hypothesized literal translation automaton and its monitoring mechanism.